Karakteristik Sensoris Kamaboko dengan Penambahan Ekstrak Purun Tikus (Eleocharis dulcis) - Baehaki, Ace; Herpandi, Herpandi; Rinto, Rinto; Rosalina, Rosalina (Seminar Nasional Lahan Suboptimal, 2018)
Baehaki et al, 2019. Sensoris Characteristic of Kamaboko Adding Purun Tikus (Eleocharis dulcis) Extract. pp. 172-175.This study aimed to determine sensory characteristics of kamaboko with the addition of extracts of purun tikus (Eleocharis dulcis). This study uses experimental laboratory methods and data analysis is carried out descriptively. The parameters observed were sensory tests which included the appearance, texture and aroma of kamaboko with the addition of purun tikus extract. The results of sensory values with the appearance parameters and aroma of kamaboko with different extract treatment and storage duration showed the value of appearance and aroma of kamaboko without the addition of extract was higher than that of kamaboko with the addition of purun tikus extract. While the texture parameters showed kamaboko with the addition of purun tikus extract had a higher textur compared to kamaboko without the addition of extract.